LOCAL ESISTENCE OF SCALARWAVE EQUATION ON THE ROBERTSON-WALKER UNIVERSE AS A BACKGROUND WITH k = 0 - IQBAL (NIM : 20215028), MUHAMMAD
In this thesis, we study about the wellposedness of scalar wave equation on Robertson- Walker universe as a background with spatial curvature k = 0. We start from nonminimal Lagrangian for scalar field on curved background with potential turned on. Then we derive the equations of motion and tensor energy-momentum. After that we specify our case to k = 0. Finally, we prove the local existence and uniqueness for the equation of motion.